Analysis of cytokinin content and associated genes at different developmental stages in pak choi (Brassica rapa ssp. chinensis Makino). Issue 1 (31st December 2022) - Bao, Yue; Li, Xuan; Qi, Xianhui; Wang, Xueting; Feng, Xianjun; Chen, Yinglong; Hou, Leiping; Li, Meilan
Abstract: Pak choi ( Brassica rapa ssp. chinensis Makino) is a typical seed vernalization vegetable. Because premature bolting in spring causes significant economic losses, it is very important to clarify the flower formation mechanism to prevent this. Cytokinins are important plant hormones involved in regulating plant growth and development. To understand the relationship between cytokinin metabolism and flowering of pak choi, in this study, we determined the cytokinin trans -zeatin content in shoot apices of pak choi at different developmental stages by enzyme-linked immunosorbent assay. The results showed that cytokinin levels increased significantly after low temperature treatment at 4 °C, and continued to increase with vegetative growth after transplanting, reaching a peak at the critical period which is immediately prior to flower buds' differentiation (S0), then decreased thereafter. The levels for low temperature treatment were consistently higher than controls. To explore the molecular mechanism underpinning the cytokinin changes, expression of homologous genes encoding cytokinin metabolic enzymes was analysed by transcriptome sequencing. The expression levels of nine genes ( Bra004037, Bra023701, Bra002204, Bra014968, Bra028326, Bra028182, Bra034022, Bra009143 and Bra005869 ) were consistent with the changes in cytokinin content. The correlation between differentially expressed genes and cytokinin content in different developmental stages of apexes was analysed, and six closely related genes ( Bra023701, Bra002204, Bra014968, Bra028182, Bra005869 and Bra009143 ) were identified. The results help to illuminate the molecular mechanisms controlling flowering of pak choi.